2021
DOI: 10.3390/su132413753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zero and Minimum Tillage on Cotton Productivity and Soil Characteristics under Different Nitrogen Application Rates

Abstract: Long-term conservation tillage and straw incorporation are reported to improve the soil health, growth, and yield traits of crops; however, little is known regarding the optimal nitrogen (N) supply under conservation tillage with straw incorporation. The present study evaluated the effects of conservation tillage practices (ZTsas: zero tillage plus wheat straw on the soil surface as such, and MTsi: minimum tillage plus wheat straw incorporated) and different N application rates (50, 100, 150, and 200 kg ha−1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Javed et al ( 2022b ) also reported that the application of various organic and inorganic compounds was responsible for improving nitrogen use efficiency. Khan et al ( 2021 ) stated that nitrogen application enhanced the growth and productivity of field crops and maintained the soil fertility status (Shah et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Javed et al ( 2022b ) also reported that the application of various organic and inorganic compounds was responsible for improving nitrogen use efficiency. Khan et al ( 2021 ) stated that nitrogen application enhanced the growth and productivity of field crops and maintained the soil fertility status (Shah et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, insufficient nitrogen intake has profound effects on food production. Some early researchers reported that the rate and timing of nitrogen application played an important role in improving the yield of rice and other field crops ( Habtergebrial et al, 2013 ; Khan et al, 2021 ). These authors found the highest yields (4–5-ton ha –1 ) of basmati rice and its components at 130–140 kg N ha –1 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that uptake of N by cotton was recorded significantly highest in ZT as compared to the CT. The adequate moisture content in ZT helped to restore high N in soil which led to improved uptake by cotton ( Khan et al, 2021 ). Similarly, the highest uptake of N, P, and K in cotton was recorded in ZT as compared to CT in the Akola region of Maharashtra ( Wagh et al, 2016 ).…”
Section: Factors Related To N Uptakementioning
confidence: 99%
“…Normally, farmers rely on the excessive application of N to enhance growth and crop yield ( Dong et al, 2012 ). Nevertheless, excessive rates of N not only outcomes in stagnant growth, prolonged crop maturity, and reduction in productivity, but also reduce NUE and environmental pollution ( Khan et al, 2021 ; Niu et al, 2021 ; Huang et al, 2022 ; Javed et al, 2022a , b ; Kumar et al, 2022 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%